PEMANFAATAN JERAMI PADI FERMENTASI DENGAN PROBIOTIK STARBIO TERHADAP PERTUMBUHAN DOMBA JANTAN LOKAL UTILIZATION OF RICE STRAW FERMENTED BY PROBIOTICS STARBIO ON THE GROWTH OF LOCAL RAMS - cory sitanggang (Universitas Sumatera Utara, 2013)
ABSTRACT Rice straw is one of the abundant agricultural by product and has alow nutrient content. To improve the nutrition value ofrice straw can be done by fermented used Starbio. The objective of this research was to analyze the benefits of rice straw fermented with probiotic Starbio on the growth of local rams. The experiment use four local rams with average body weight 11,87 ± 1,98 kg was conducted in Laboratory of Animal Biology Livestock Studies Program, Faculty of Agriculture,University of Sumatera Utara. Design of research used a latin square design with 4 treatments, which are P0: concentrate + control (unfermented rice straw); P1: concentrate + 0,4 kg Starbio+ 0.4 kg Urea/ 100 kg rice straw; P2: concentrate+ 0.6 kg Starbio + 0.6 kg Urea/ 100 kg rice straw; P3: concentrate + 0.8 kg Starbio +0.8 kg Urea/ 100 kg rice straw. The parameters were feed consumption, body weight gain and feed conversion. The results showed the average feed intake were (g/head/day) (497.62; 492.83; 517.89 and 499.6, respectively). Average weight gain (g/head/day) (20.833; 19.500; 21.750 and 21.083, respectively). Average feed conversion (23.95; 25.22; 23.80 and 23.73, respectively). The conclusion showed that various levels of Starbio were not significant different for all of the parameters were feed consumption, body weight gain and feed conversion of local rams. Keywords: Local rams, rice straw, Starbio, fermented and performance